SURVEI RUMAH SEHAT DI KOTA PALEMBANG TAHUN 2007 - Ekowati Retnaningsih (Publikasi Penelitian Terapan dan Kebijakan, 2020)
The presence of house that healthy, secure, suitable, regular is very needed so that the functions and advantages of the house can be fulfilled well and can give healthy influence to the occupants in the house. The objection of this research was to know proportion of healthty house in each kecamatan in Palembang so we can set the right planning to the right target. This research use quantitative paradigm and it use cross sectional design. The sampling method was done by multistage randomsampling in all kecamatan in Palembang, that are 103 kelurahan. With estimate the possibilities of drop out sample is 5%, so the minimal sample amount that needed were 9.496 houses. Based on the descriptive analysis result in this research, we can conclude that kecamatan with proportion of healthty house is > 80 % are: 1) roof: 2 kecamatan, 2) floor: 14 kecamatan, 3) wall: 14 kecamatan, 4) ventilation: 9 kecamatan, 5) clean water source: 7 kecamatan, 6) family lavatory: 10 kecamatan, 7) SPAL: 1 kecamatan, 8) Garbage can: 1 kecamatan. Community knowledge about healthy environment that already good has reach > 80 % only 3 kecamatan and defecate bahaviour in lavatory that already reach > 80 % are 13 kecamatan.